'Educare' in Australia: analysing policy mobility and transformation. Issue 2 (2nd April 2016) - McShane, Ian
Abstract: Background: Early childhood education and care has been an area of significant policy attention, public investment and private market activity in Australia over the past three decades. Australian educationists and policy-makers have looked to international examples for evidence, policy design and institutional models. However, this area is under-researched in Australia, with regard to how these knowledge flows are theorised, and how policy is implemented on the ground. Purpose: The paper's purpose was to contribute new Australian-focussed conceptual and empirical insights on the trajectories, development and implementation of evidence-based policy in the field of early childhood education and care. Sources of evidence: The paper is based on three main sources of evidence: the critical literature on policy transfer and policy mobility policy statements, reports and planning documents produced by national- and state-level governments data from fieldwork analysis of new capital works and programmes in the early childhood field. Main argument: International research and evidence on the benefits of investment in early learning has had a significant impact on the framing of Australian policy. So too has a move in several countries to align early childhood institutions with schools. However, a dominant paradigm of policy transfer, reliant on pluralist and rationalist frameworks of policy-making, fails to account for the dynamics of policy development and implementation across and within jurisdictions and geographical space. Conceptualising a new alignment in Australia between children's centres and schools as 'educare', this article employs the theoretical lens of policy mobility to account for the circulation and transformation of educare policy in Australian settings. Through an empirical analysis of a new educare centre in the growth corridor of western Melbourne, the article demonstrates the extent to which neoliberal policy settings outside the educational sphere, around public finance, partnership, place and infrastructure provision, influence the implementation of 'educare' policy. Conclusions: The educare discourse in Australia addresses a complex and multiscalar set of policy problems that associate child development with concerns around human capital formation, economic efficiency and productivity, place making and community building, and the role of the public sector in neoliberal democracies. International circuits of knowledge, policy design and institutional models in the educare field have been significant in shaping recent Australian policy, despite well-publicised views expressed in Australia on the disconnection between academic research and policy. The strength of policy mobility as a theoretical lens to assist our understanding of these influences lies in its critique of formalism in policy-making and in its attention to fluidity and transformation. The mobility lens encourages new empirical research that focuses on spatial and institutional dynamics, assisting our reading of on-the-ground developments in Australia's fastest growing city.